2005
DOI: 10.1016/j.jcp.2005.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A new parallel strategy for two-dimensional incompressible flow simulations using pseudo-spectral methods

Abstract: A novel parallel technique for Fourier-Galerkin pseudo-spectral methods with applications to two-dimensional Navier-Stokes equations and inviscid Boussinesq approximation equations is presented. It takes advantage of the programming structure of the phase-shift de-aliased scheme for pseudo-spectral codes, and combines the task-distribution strategy [Z. Yin, H.J.H. Clercx, D.C. Montgomery, An easily implemented task-based parallel scheme for the Fourier pseudo-spectral solver applied to 2D Navier-Stokes turbule… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In the GKV code, perpendicular dynamics is solved by using the spectral method [3] with Fast Fourier Transform (FFT) algorithms [4]. The most commonly used parallel multi-dimensional FFT is the transpose-split method [5], and one can find many literatures about the spectral or pseudo-spectral methods with parallel FFTs (e.g., 2D FFTs [6], 3D FFTs with the slab decomposition [7] and with the pencil decomposition [8]). While the transpose communications may degrade scalability, it is reported that the overlap of communications and computations improves efficiencies [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the GKV code, perpendicular dynamics is solved by using the spectral method [3] with Fast Fourier Transform (FFT) algorithms [4]. The most commonly used parallel multi-dimensional FFT is the transpose-split method [5], and one can find many literatures about the spectral or pseudo-spectral methods with parallel FFTs (e.g., 2D FFTs [6], 3D FFTs with the slab decomposition [7] and with the pencil decomposition [8]). While the transpose communications may degrade scalability, it is reported that the overlap of communications and computations improves efficiencies [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…They studied the same problem using the exponential spectral filter on a N =1500 2 grid. Yin et al 6 also used the same exponential spectral filter in their parallel fast Fourier transform (PFFT) scheme using larger number of grid points false(N=40962false). Different dealiasing schemes are implemented with the classical RK4 temporal scheme to test the resolving capability of capturing the sharp density gradient within a unstable bubble using just adequate spatial resolution N =512 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We will show that numerical results obtained from the RK4‐based RPSM scheme displays lesser parasitic currents. We have used the same initial conditions used in References 6,50 for comparison purposes. The initial conditions for solving the 2D inviscid Boussinesque equations are as follows 6,50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To find out the nonstationary solutions of this nonlinear differential equation, we use here pseudo spectral method. 25 Nordsieck predictor-corrector method has been used for time-stepping. As pseudo spectral method is used here, to avoid the aliasing error, there are several methods which one can use, such as 3 2 -rule, 26 2 ffiffi 2 p 3 -rule, 27 2 3 -rule (zero-padding method).…”
Section: Linear Regimementioning
confidence: 99%